Pengaruh Pembelajaran melalui Audio Visual terhadap Tingkat Keseimbangan Fokus Belajar Mahasiswa Aktif BPI UIN Jakarta - Indriani, Yundari; Aidah, Luluatul; Ridho, Muhammad; Valentina, Nisrina (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to analyze the influence of learning through audiovisual media on the balance level of students’ study focus. Audiovisual media is considered capable of increasing students’ concentration and engagement in the learning process by stimulating the senses of sight and hearing simultaneously. The research method used was quantitative with an experimental approach, involving a number of students as the research sample. Data were collected through observations of learning focus and learning outcome tests before and after the application of audio visual media. The results of the study showed that learning using audiovisual media significantly improved students’ learning focus balance compared to conventional learning methods. Additionally, audiovisual media also enhances motivation and thorough understanding of the material. These findings support the use of audiovisual media as an effective learning strategy to create a more interactive and optimal learning atmosphere. The implications of this study are expected to provide a reference for educators in developing innovative and adaptive learning methods to students’ needs.